ByzRev 06.2024.076: Anthony Kaldellis, The Case for East Roman Studies: (Past Imperfect). Leeds: Arc Humanities Press 2024. - Theodoropoulos, Panagiotis (The Byzantine Review, 2024)
Anthony Kaldellis, The Case for East Roman Studies (Past Imperfect). Leeds: Arc Humanities Press 2024. 105 pp. – ISBN 978-1-80270-182-1